The Yamasee Indians from Florida to South Carolina - Bossy, Denise I. (University of Nebraska Press, 2018)
"Archaeologists of South Carolina and Florida, historians of the Native South, Spanish Florida, and British Carolina address elusive questions about Yamasee identity, political and social networks, and the fate of the Yamasees after the Yamasee War"--